Clinical predictors of radiological pneumonia: A cross-sectional study from a tertiary hospital in Nepal - Shrestha, Sandeep; Chaudhary, Nagendra; Shrestha, Saneep; Pathak, Santosh; Sharma, Arun; Shrestha, Laxman; Kurmi, Om P. (PloS one, 2020)
Background Despite readily availability of vaccines against both Hemophilus influenzae and Pneumococcus, pneumonia remains the most common cause of morbidity and mortality in children under the age of five years in Nepal. With growing antibiotic resistance and a general move towards more rational antibiotic use, early identification of clinical signs for the prediction of radiological pneumonia would help practitioners to start the treatment of patients. The main aim of this study was to reassess the clinical predictors of pneumonia in Nepal. Methods This cross-sectional study was conducted between June 2015 and November 2015 at Tribhuvan University Teaching Hospital, a tertiary hospital in Kathmandu, Nepal. Children aged 3–60 months with a clinical diagnosis of pneumonia by a physician were enrolled in the study. Radiological pneumonia was identified and categorized as per World Health Organization guidelines by an experienced radiologist blinded to patient characteristics. We calculated sensitivity and specificity of clinical signs and symptoms for radiological pneumonia. Results Out of 1021 children with fever, 160 cases were clinically diagnosed as pneumonia and were enrolled for this study. Among the enrolled patients, 61% had radiological pneumonia. Tachypnea had the highest sensitivity of 99%, while bronchial breathing had the highest specificity of 100%. During univariate analysis, grunting, wheezing, nasal discharge, decreased breath sounds, noisy breathing and hypoxemia were associated with radiological pneumonia. Only hypoxemia remained an independent predictor when adjusted for all the factors. Conclusion Tachypnea was the most sensitive sign, whereas bronchial breathing was most specific sign for radiological pneumonia.